Protein O-fucosylation in Plasmodium falciparum ensures efficient infection of mosquito and vertebrate hosts - Sash Lopaticki (Nature Portfolio, 2017)
The role of O-glycosylation in the malaria life cycle is largely unknown. Here, the authors identify a Plasmodium protein O-fucosyltransferase and show that it is important for normal trafficking of a subset of surface proteins, particularly CSP and TRAP, and efficient infection of mosquito and vertebrate hosts.